GE_GERICHTE P/13605/2020 vom 25. Juli 2024 - GE Cour de justice (2024)
EXPULSION(DROIT PÉNAL);DISPOSITIONS PÉNALES DE LA LCR;FIXATION DE LA PEINE | CP.123; CP.180; LJAr.130; LArm.33; CP.252; CP.251; LEI.117; LCR.95; LCR.90; CP.303; CP.177